Sources of Anxiety among Physical Fitness Coaches in Jordan - Akour, Ahmad Abed Alwahab; Akour, Mohammed (Journal of Posthumanism, 2025)
The purpose of the study is to determine the sources of anxiety among physical fitness coaches in Jordan, as well as to identify the difference in sources of anxiety according to study variables (gender, experience years, specialization). The study sample was comprised of (122) male and female coach, out of (130) coach in Jordan. The researcher used the descriptive approach as a survey by applying the questionnaire to the sample to obtain the necessary data, and after conducting the necessary statistical treatments, the results indicated that the degree of anxiety among physical fitness coaches was of a medium degree and their sources of anxiety were ordered as following (The field of self- threat, colleagues, (capabilities and facilities) and (ambiguity and unknown), and finally social assessment). The results also indicated that there were no statistically significant differences according to the study variables (gender, experience years, and specialization). The researcher believes that there are many sources of anxiety facing physical fitness coaches during their job in many fields, therefore the researcher believes that it is necessary to highlight the category of physical fitness coaches and work to improve their living conditions and hold workshops that develop their self-confidence and alleviate the sources of anxiety they are exposed to.